Students’ Experiences, Reactions and Opinions on Bullying at Esperanza National High School, Esperanza, Sultan Kudarat, Region XII, Philippines - Rodalyn O. Lapada; Elmar S. Lapada (Randwick International of Education and Linguistics Science Journal, 2021)
This study was conducted to determine students’ experiences, reactions and opinions on bullying. It used a descriptive research design wherein students’ experiences, reactions and opinions were gathered through survey questionnaires. Purposive sampling technique was employed using snowball sampling technique. Online survey questionnaire was sent to the selected students via messenger. These students forwarded the online survey questionnaire to those students who they thought potential respondents of the study via messenger too. Finding revealed that Esperanza National High School has maintained a healthy school environment suited to the different types of learners since the bullying was less evident in the school. Occasional occurrence of bullying in the school prompted the students to rarely report the incidence to the concerned people. Students very seldom experienced the bullying from the people they frequently engaged and communicated. They normally responded to the minor incidence of bullying they experienced from the school or at home. They believed that bullying has a less extent of effect on their personal development. It is, indeed, recommended that Esperanza National High School should sustain building a positive school environment and should maintain the zero tolerance of any bullying incidence in the school.